A interdisciplinaridade entre as disciplinas de física e matemática - Ricardo, Marcos Antônio (2022)
The objective of the work was to analyze how the interdisciplinarity between the disciplines of Physics and Mathematics can help in the resolution of activities with students of the 9th year of Elementary School. Regarding the methodology, a literature review and field research were carried out. The activities were applied in the classroom at a municipal school located in the city of São Paulo. After conducting classes that addressed the initial concepts of scalar kinematics and Newton's Laws, activities on scalar kinematics and Newton's Laws were proposed to 10 9th grade students. After the application of the activities, it was observed that many students, even though they knew the formulas to be used for the development of the problems, ended up making them wrong, because they were not able to proceed with the development of mathematical calculation. It is concluded that it is recommended to have more interdisciplinary activities.